Rudimentary Myelomeningocele: A Rare Case Report and Literature Review - Gautam, P; Goel, RG; Kapoor, AK; Gupta, SN; Ghimire, PG; Bharti, SV (Journal of Nepalgunj Medical College, 2015)
Rudimentary meningocele, in which meningothelial elements occupy most of a solid skin-covered mass, is extremely rare. Most reported rudimentary meningocele were on the midline scalp, preferentially involving the occiput and vertex. A 10 yearold child who presented with rudimentary myelomeningocele in the midline at the level of T7-T8 is reported. We believe this is the first reported case of a rudimentary myelomeningocele at this site. Journal of Nepalgunj Medical College Vol.12(1) 2014: 39-40